Beginning Spanish ¡Empecemos por aquí! - Ceciliano, Jenny; Notman, Lisa (Open textbook library., 2022)
Beginning Spanish ¡Empecemos por aquí! focuses on the development of communication skills in interpretive, interpersonal, and presentational modes while centering student voices. Activities engage learners in real exchanges of information on topics that are relevant to adult students. In addition to language-acquisition learning outcomes, this text supports learning outcomes in diversity, equity, inclusion, cultural sustainability, and social justice.